Catalytic Thermal Liquefaction of Oil Shale in Tetralin. (18th July 2012) - Johannes, I.; Tiikma, L.; Luik, H.; Tamvelius, H.; Krasulina, J.
Abstract : A short review on the publications concerning thermal liquefaction of solid fuels in the environment of hydrogen donor solvents and catalysts is compiled. New experimental results on the catalytic thermal dissolution of oil shale in tetralin as the hydrogen donor solvent in a batch autoclave are presented. The impacts of pyrolysis temperature, duration, and catalyst type on the yields of gas, maltenes, asphaltenes, preasphaltenes, and coke in the presence of tetralin are described.